Pengaruh Peran Orang Tua Terhadap Hasil Belajar Matematika Siswa SMP IT Wihdatul Ummah Kolaka di Masa Pandemi Covid-19 - Fitriyani Hali; Novianti; Halidin; Deti Sri Rahayu; Dian Ulfa Sari (Arden Jaya Publisher, 2022)
The formulation of the problem in this research are: 1) This research is focused on seeing how the role of parents in the mathematics learning outcomes of Wihdatul Ummah Kolaka Islamic Junior High School students during the covid 19 pandemic. 3) Is there an influence of the role of parents on the mathematics learning outcomes of Wihdatul Ummah Kolaka Islamic Junior High School students during the covid 19 pandemic. This research is an expost facto study. The population in this study were all class VIII SMP IT Wihdatul Ummah Kolaka as many as 51 students. Using This research is an ex post facto research. The population in this study were all VIII SMP IT Wihdatul Ummah Kolaka as many as 51 students. Using saturated sampling technique, a sample of 51 students was obtained. Data collection techniques using questionnaires and documentation. Data analysis used simple linear regression analysis. Based on the results of data processing and discussion in this study, several conclusions were obtained as follows: (1) The Role of Parents of Class VIII SMP IT Wihdatul Ummah Kolaka obtained the lowest score of 34.38, the highest score of 87.5, the average value of 70, 86 and the standard deviation of 8.85; (2) Student learning outcomes of VIII SMP IT Wihdatul Ummah Kolaka obtained the lowest score of 40, the highest score of 89, the average value of 69.75 and the standard deviation of 8.17; (3) There is a positive and significant influence on the role of parents on mathematics learning outcomes for class VIII SMP IT Wihdatul Ummah Kolaka with a contribution value of 57.7%.